2021
DOI: 10.1371/journal.pgen.1009687
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Derlin activity suppresses Notch-dependent tumours in the C. elegans germ line

Abstract: Regulating the balance between self-renewal (proliferation) and differentiation is key to the long-term functioning of all stem cell pools. In the Caenorhabditis elegans germline, the primary signal controlling this balance is the conserved Notch signaling pathway. Gain-of-function mutations in the GLP-1/Notch receptor cause increased stem cell self-renewal, resulting in a tumor of proliferating germline stem cells. Notch gain-of-function mutations activate the receptor, even in the presence of little or no li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 129 publications
(262 reference statements)
0
5
0
Order By: Relevance
“…The association of NOD1 and NOD2 with proinflammatory responses induced by IRE1α/TRAF2 signaling provides a novel link between innate immunity and ER stress-induced inflammation ( 30 ). The activation of UPR caused by ER stress may help to correct the increased level of GLP-1/Notch signaling and the associated overproliferation in the germ line of C. elegans ( 31 ). The ss-GSEA results demonstrate a significant relationship between the prediction signatures and dendritic cell activation, immature dendritic cells, immune status of the Treg, and dendritic cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…The association of NOD1 and NOD2 with proinflammatory responses induced by IRE1α/TRAF2 signaling provides a novel link between innate immunity and ER stress-induced inflammation ( 30 ). The activation of UPR caused by ER stress may help to correct the increased level of GLP-1/Notch signaling and the associated overproliferation in the germ line of C. elegans ( 31 ). The ss-GSEA results demonstrate a significant relationship between the prediction signatures and dendritic cell activation, immature dendritic cells, immune status of the Treg, and dendritic cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Derlin family proteins: Singh et al demonstrated that reduced CUP-2 and DER-2 function suppresses GLP-1/Notch-mediated germline tumorigenesis [ 22 ]. CUP-2 and DER-2 are Derlin family proteins that function in endoplasmic reticulum (ER)-associated degradation (ERAD).…”
Section: Glp-1/notch-activation-mediated Tumorigenesis: Ectopic Proli...mentioning
confidence: 99%
“…They also found that the suppression of GLP-1/Notch-mediated germline tumorigenesis by the cup-2 mutation requires a proper Unfolded Protein Response (UPR) function. Therefore, they suggest that reduced Derlin activity may suppress GLP-1/Notch-mediated tumorigenesis through the activation of ER stress and UPR [ 22 ].…”
Section: Glp-1/notch-activation-mediated Tumorigenesis: Ectopic Proli...mentioning
confidence: 99%
“…Derlin family proteins: Singh et al demonstrated that reduced CUP-2 and DER-2 function suppresses GLP-1/Notch-mediated germline tumorigenesis[21]. CUP-2 and DER-2 are Derlin family proteins that function in endoplasmic reticulum-associated degradation (ERAD).…”
mentioning
confidence: 99%
“…CUP-2 and DER-2 are Derlin family proteins that function in endoplasmic reticulum-associated degradation (ERAD). Therefore, they suggest that Derlin activity may be associated with GLP-1/Notch-mediated tumorigenesis[21].  U/T level: Chi et al demonstrated that GLP-1 expression in the distal gonad region is repressed by low Uridine/Thymidine (U/T) levels[22].…”
mentioning
confidence: 99%